2016
DOI: 10.1186/s13662-016-0985-1
|View full text |Cite
|
Sign up to set email alerts
|

A pest management model with state feedback control

Abstract: In this paper, research of a class of state feedback control model which is mainly used in crop pests management, with Bendixson-Dulac discriminance, proves that this model has an unique and globally stable positive equilibrium under the weak time-delay kernel function. Also, we adopt the subsequent function method in the ordinary differential equation of the geometric theory to prove that a sufficient condition holds for the existence of an order one period solution in the system. At the same time, it also pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Note that if ≤ 0, then for any + ≥ 0, (17) and (18) are well defined. Actually, if we denote ( ) = −( / ) exp(−( / ) ), then it can easily be shown that…”
Section: Poincaré Map Let a Trajectory Initiate With Initial Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Note that if ≤ 0, then for any + ≥ 0, (17) and (18) are well defined. Actually, if we denote ( ) = −( / ) exp(−( / ) ), then it can easily be shown that…”
Section: Poincaré Map Let a Trajectory Initiate With Initial Valuementioning
confidence: 99%
“…There are two main kinds of the classical impulsive differential equations: fixed-time impulse and state-dependent impulse. We refer readers to [12][13][14][15][16][17][18][19][20][21][22][23][24] for more details about the aforementioned kinds of classical impulsive differential equations and their application in different fields.…”
Section: Introductionmentioning
confidence: 99%
“…For a long term in this way, the predator will be endangered, the ecological balance will also be destroyed. To avoid such a disaster, intervention has to be made, such as pest management and harvesting of fish [6][7][8][9][10][11][12][13][14][15]. Such interventions can be mathematically modeled by impulsive systems.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the theoretical studies on IDES have produced a lot of good research results [23][24][25][26][27][28][29][30][31][32][33][34]. Based on the theoretical research, some scholars have introduced impulsive differential equations in Lotka-Volterra system such as the regular release of predators [35][36][37]; the periodic release of infected pests [38][39][40]; the periodic release of predators together with regular spray of pesticides [41][42][43]; the periodic release of predators and infected pests together with regular spray of pesticides [39,44]. In the practical application, the two control measures can be adopted at two different levels of pest density concerning this case.…”
Section: Introductionmentioning
confidence: 99%